2020
DOI: 10.1007/s10389-020-01405-w
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular health care and health literacy among immigrants in Europe: a review of challenges and opportunities during the COVID-19 pandemic

Abstract: Objectives Europe is a destination for many migrants, a group whose proportion of the overall population will increase over the next decades. The cardiovascular (CV) risk distribution and outcomes, as well as health literacy, are likely to differ from the host population. Challenges related to migrant health status, cardiovascular risk distribution and health literacy are compounded by the ongoing coronavirus disease 2019 (COVID-2019) crisis. Methods We performed a narrative review of available evidence on m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 62 publications
(82 reference statements)
4
14
0
Order By: Relevance
“…33 Therefore, their lifestyles may differ. 31 Moreover, our study indicated that social support was a reinforcing factor for HL among older adults, similar to other studies. Social support from neighbors is important to older adults, particularly those in Asian countries.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…33 Therefore, their lifestyles may differ. 31 Moreover, our study indicated that social support was a reinforcing factor for HL among older adults, similar to other studies. Social support from neighbors is important to older adults, particularly those in Asian countries.…”
Section: Discussionsupporting
confidence: 90%
“…The sample population’s residence in urban or semiurban settings may have resulted in a better quality of life related to education level, living conditions, and access to information. 31 ) Although older adults in rural communities receive more support, many areas were locked down and activities canceled. 32 ) However, women were one of the most vulnerable populations during the pandemic and often had less access to information compared to men.…”
Section: Discussionmentioning
confidence: 99%
“…With routine services closed due to the pandemic, concerns have been raised that migrants have struggled to navigate the new systems ( Doctors of the World 2020 , Valeriani et al, 2020 , Esegbona-Adeigbe, 2020 , Nobody Left Outside 2020 ) and it has exacerbated migrants’ exclusion from health services ( Desai and Samari, 2020 , Santos et al, 2020 , Aragona et al, 2020 , Clarke et al, 2020 , Devillanova et al, 2020 ). Migrants may experience challenges in accessing healthcare remotely ( Doctors of the World 2020 , Brickhill-Atkinson and Hauck, 2020 , Page et al, 2020 , Langellier, 2020 , Wernly et al, 2020 ); however, telemedicine may also offer opportunities that need to be further explored in these populations ( Warner et al, 2020 , Green et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…With routine services closed due to the pandemic, concerns have been raised that migrants have struggled to navigate the new systems (50, 113–115) and it has exacerbated migrants’ exclusion from health services (116120). Migrants may experience challenges in accessing healthcare remotely (50, 63, 101, 106, 121); however, telemedicine may also offer opportunities that need to be further explored in these populations (122, 123).…”
Section: Resultsmentioning
confidence: 99%